2020
DOI: 10.5194/acp-2020-161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Chemical Composition of Gas and Particle Phase Products of Aromatic Oxidation

Abstract: Abstract. Aromatic volatile organic compounds (VOC) are key anthropogenic pollutants emitted to the atmosphere and are important for both ozone and secondary organic aerosol (SOA) formation in urban areas. Recent studies have indicated that aromatic hydrocarbons may follow previously unknown oxidation chemistry pathways, including autoxidation that can lead to the formation of highly oxidised products. In this study we evaluate the gas and particle phase ions formed during the hydroxyl radical oxidation of sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 84 publications
(134 reference statements)
0
19
0
Order By: Relevance
“…As discussed in Section 4.2.1, these lightly oxygenated molecules can be directly emitted from anthropogenic and biogenic sources or come from oxidation processes of various VOC precursors (Conley et al, 2005;Pandya et al, 2006;Rantala et al, 2015;Hartikainen et al, 2018). For instance, C7H10O has been found from direct soil emissions (Abis et al, 2020) or oxidation processes of 1,2,4-trimethyl benzene (Mehra et al, 2020). Therefore, we expect the molecules in this factor to be either directly emitted or as oxidation products of forest emissions.…”
Section: Factor S2: Monoterpenesmentioning
confidence: 99%
“…As discussed in Section 4.2.1, these lightly oxygenated molecules can be directly emitted from anthropogenic and biogenic sources or come from oxidation processes of various VOC precursors (Conley et al, 2005;Pandya et al, 2006;Rantala et al, 2015;Hartikainen et al, 2018). For instance, C7H10O has been found from direct soil emissions (Abis et al, 2020) or oxidation processes of 1,2,4-trimethyl benzene (Mehra et al, 2020). Therefore, we expect the molecules in this factor to be either directly emitted or as oxidation products of forest emissions.…”
Section: Factor S2: Monoterpenesmentioning
confidence: 99%
“…3 shows the proportion of mass spectral signal of each factor attributable to ion formulae measured during the aromatic oxidation experiments classied as ring-retaining (C 6 -C 9 and double bound equivalent (DBE)$ 4). 1 This analysis indicates that the PM-NOA has the largest potential contribution from aromatic SOA products (26%), followed by AM-NOA (19%) and NT-NOA (16%). It should be noted that these contributions do not include nitro-aromatics which were not observed by Mehra et al (2020) 1 due to the lower HO 2 : NO ratios employed in these experiments.…”
Section: Comparison With Aromatic Soamentioning
confidence: 91%
“…77 Recently, we studied the composition of SOA from several aromatic hydrocarbons using a FIGAERO-CIMS and identied a suite of ring-retaining products, including HOM, which contributed up to 43% of observed signal from single component aromatic experiments. 1 Here we compare the ions observed in the ambient factors with those from this aromatic study to estimate the potential contribution that aromatics could have to measured SOA in Beijing. As discussed in Mehra et al (2020), 1 many ions observed from aromatics have ion formulas concurrent with products from oxidation of other precursors.…”
Section: Comparison With Aromatic Soamentioning
confidence: 99%
See 2 more Smart Citations